Complications from the use of peroxides - Briso, André Luiz Fraga [UNESP]; Rahal, Vanessa [UNESP]; Gallinari, Marjorie Oliveira [UNESP]; Soares, Diana Gabriela [UNESP]; Costa, Carlos Alberto de Souza [UNESP] (Springer Nature, 2016)
While dental whitening or dental bleaching is one of the most popular aesthetic procedures, dentists should base their decision to prescribe peroxide-based whitening agents on evidence-based techniques and regimens. The contact of bleaching products with the mucosa, dental tissues, and preexisting restorations may trigger a series of adverse effects both on soft and hard tissues. This chapter details the precautions that must be taken prior to prescribing different bleaching therapies with the goal of improving the patient’s smile, without damaging oral tissues.Additionally, this chapter will discuss tooth sensitivity, which is the most common side effect of any bleaching treatment. The prevention of tooth sensitivity is of upmost importance to avoid discomfort to patients and increase patient’s compliance.